THE EFFECT OF USING SUGAR CANE WASTE ON CONCRETE FLEXURAL STRENGTH - FAJAR RIVANI; SAHAT MARTUA SIHOMBING; INDRIASARI (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2024)
Modern construction technology has developed with the principle of environmental concern, integrating natural materials into construction materials to support environmentally friendly practices. Green construction includes processes that minimize the use of hazardous materials, do not disturb the peace of the population, limit waste production, maintain the balance of nature, and avoid the use of hazardous chemicals. In industry, rapidly developing technology often produces negative waste. Population growth increases the need for construction materials from natural and artificial sources. One solution is the utilization of local resources, including waste and garbage, which not only reduce pollution but also as an alternative to conventional building materials, such as the use of bagasse waste in construction. Based on data analysis and conversations that have been described in the previous chapter regarding the use of bagasse waste with variations of 0%, 10%, and 15%, the results of the flexural test of fc'25 concrete, namely after 28 days, the strength of ordinary concrete is 3.67 MPa, while variation 1 with 10% bagasse reaches 4.06 MPa, while for variation-2 with 15% bagasse reaches 4.49 MPa. The test results appear to meet the minimum requirements of 14% of the planned concrete compression test. The increase with the addition of sugarcane pulp was an average of 10%.